Race may modify the association between blood type and COVID‐19 infection. Issue 3 (30th July 2022) - Luo, Jiajun; Craver, Andrew; Zakin, Paul; Stepniak, Liz; Moore, Kayla; King, Jaime; Kibriya, Muhammad G.; Johnson, Julie; Olopade, Christopher O.; Pinto, Jayant M.; Kim, Karen; Ahsan, Habibul; et al.
Abstract: This study aims to investigate the race/ethnicity‐specific association between blood type and COVID‐19 susceptibility during March, 2020 and December, 2021 using data from the electronic health record at the University of Chicago Medicine. The study population was stratified into four groups: non‐Hispanic White, non‐Hispanic Black, Hispanic, and other. Log‐binomial generalized mixed model was used to estimate the relative risk (RR) and 95% confidence interval (CI). When compared to blood type O, type B was associated with positive COVID‐19 test in Blacks (RR = 1.12, 95% CI: 1.02–1.23), Whites (RR = 1.28, 95% CI: 0.99–1.66), and Hispanic (RR = 1.36, 95% CI: 0.97–1.92).